ON THE MOMENTS OF ORDER STATISTICS FROM DISCRETE DISTRIBUTIONS - Calik, Sinan; Gungor, Mehmet; Colak, Cemil (Isoss Publ, 2010)
In this paper, the mth raw moments of order statistics from discrete distributions are obtained. By using the mth raw moments, a relation between the moments of sample maximum of order statistics from a discrete uniform distribution and the sum S(N-1, n) is obtained. It is shown that with the help of this relation, one can obtain all the moments for sample maximum of order statistics from a discrete uniform distribution. By using MATLAB, we compute the means and variances of the sample maximum order statistics for sample size N = 10(10) 50(50) 100 and n = 1(1) 10. Further studies may focus on a software program computing the means and variances of sample maximum of order statistics from any discrete distributions.
Keywords: Order statistics; Discrete distribution; Moment; Sum; Uniform distribution